2005
DOI: 10.1074/jbc.m406391200
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-3a-dependent Cell Motility Involves RhoA Activation and Is Specifically Regulated by Dishevelled-2*[boxs]

Abstract: Wnts stimulate cell migration, although the mechanisms responsible for this effect are not fully understood. To investigate the pathways that mediate Wnt-dependent cell motility, we treated Chinese hamster ovary cells with Wnt-3a-conditioned medium and monitored changes in cell shape and movement. Wnt-3a induced cell spreading, formation of protrusive structures, reorganization of stress fibers and migration. Although Wnt-3a stabilized ␤-catenin, two inhibitors of the ␤-catenin/canonical pathway, Dickkopf-1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 53 publications
5
81
0
1
Order By: Relevance
“…It is also known that the b-catenin/Tcf target gene fra-1 directly induces MMP-1 and MMP-9 promoter activity (Belguise et al, 2005). Our quantitative RT-PCR data showed that the expression levels of CD44v8-9 and MT1-MMP were decreased after FZD7_siRNA transfection into HCT-116 cells ( Figure 2F signalling, Dickkopf (DKK)-1 and a dominant-negative Tcf construct, did not reduce Wnt3a-dependent motility of CHO-K1 cells (Endo et al, 2005), and that DKK-1 and DKK-2 had no effect on Wnt3a-induced migration of myeloma cells (Weeraratna et al, 2002). In the former cell model system, RhoA was also activated with Wnt3a, whereas the activation of PKC family proteins including PKCa, PKCb and PKCm as well as RhoA was found in the latter.…”
Section: Discussionmentioning
confidence: 69%
“…It is also known that the b-catenin/Tcf target gene fra-1 directly induces MMP-1 and MMP-9 promoter activity (Belguise et al, 2005). Our quantitative RT-PCR data showed that the expression levels of CD44v8-9 and MT1-MMP were decreased after FZD7_siRNA transfection into HCT-116 cells ( Figure 2F signalling, Dickkopf (DKK)-1 and a dominant-negative Tcf construct, did not reduce Wnt3a-dependent motility of CHO-K1 cells (Endo et al, 2005), and that DKK-1 and DKK-2 had no effect on Wnt3a-induced migration of myeloma cells (Weeraratna et al, 2002). In the former cell model system, RhoA was also activated with Wnt3a, whereas the activation of PKC family proteins including PKCa, PKCb and PKCm as well as RhoA was found in the latter.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, we showed the remarkable increase of phosphorylation of both Dvl2 and Dvl3 in the presence of FZD10. Among the diverse signal transduction pathways mediated by Dvls, regulation of small GTPase activity and following rearrangement of actin cytoskeleton is one of the most important cellular processes, including development, neurite retraction (Kishida et al, 2004), cell motility, migration (Endo et al, 2005), etc. As it has been reported that several kinases for the phosphorylation of the Dvl family are involved in response to ligand stimulation (Hino et al, 2003;Kinoshita et al, 2003; , we screened a possible candidate kinase(s) by treating a variety of kinase inhibitors, and found that the treatment of CK1-specific inhibitor, D4476, effectively suppressed the phosphorylation of Dvl2 and Dvl3.…”
Section: Discussionmentioning
confidence: 99%
“…As the Dvl family is known to be involved in the regulation of the actin cytoskeleton structure (Capelluto et al, 2002;Endo et al, 2005;Wechezak and Coan, 2005), we examined actin fibers in cells with or without FZD10 expression by immunocytochemical analysis. The actin stress fiber was completely disassembled in HuBM-Bmi1-hT-immortalized mesenchymal stem cells transfected with FZD10 ( Figure 2a; ii and iv) as well as in FZD10-introduced 1273/99 cells (Figure 2a; vi and viii), whereas it was well assembled in their parental cells (Figure 2a;i,iii,v and vii).…”
Section: Disruption Of Actin Cytoskeleton By Fzd10 Overexpressionmentioning
confidence: 99%
“…Finally, Wnt8c and b-catenin, which are expressed in Hensens node and which regulate L/R axis formation in the chick, are able to directly induce Nodal expression (Rodriguez-Esteban et al, 2001). In addition to maintaining stem cell identity, other significant biological activities that are shared by Wnts and Cripto-1 are their ability to stimulate cell motility, invasion and EMT, as previously discussed in this review Bianco et al, 2003;Kemler et al, 2004;Strizzi et al, 2004;Endo et al, 2005;Yook et al, 2005). Loss of cell-cell adhesion due to a reduction in E-cadherin expression, possibly through Wnt/Cripto-1 crosstalk, may also affect the integrity of the stem cell niche since cell adhesion between supporting niche cells and stem cells is required for stem cell survival and asymmetric cell division (Matsui and Okamura, 2005;Yamashita et al, 2005).…”
Section: In Vivo Tumorigenesis Induced By Cripto-1mentioning
confidence: 99%